2019
DOI: 10.1111/cas.13985
|View full text |Cite
|
Sign up to set email alerts
|

A disintegrin and metalloprotease 23 hypermethylation predicts decreased disease‐free survival in low‐risk breast cancer patients

Abstract: A Disintegrin And Metalloprotease 23 ( ADAM 23), a member of the ADAM family, is involved in neuronal differentiation and cancer. ADAM 23 is considered a possible tumor suppressor gene and is frequently downregulated in various types of malignancies. Its epigenetic silencing through promoter hypermethylation was observed in breast cancer ( BC ). In the present study, we evaluated the prognostic significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Furthermore, the gene levels of a disintegrin and metalloprotease 23 (ADAM23) in central memory B cells, Fc fragment of IgA receptor (FCAR) and L1 cell adhesion molecule (L1CAM) in macrophages, adenylate cyclase activating polypeptide 1 (ADCYAP1) and sialic acid binding Ig-like lectin 6 (SIGLEC6) in mast cells, and GATA binding protein 3 (GATA3) in Th2 cells were found to increase ( Figure 2D ). Among them, ADAM23 is considered to be a possible tumor suppressor gene and is often downregulated in various malignant tumors ( Zmetakova et al, 2019 ). In addition, we used the cancer testis antigen (CTA) immune scoring system to score CTNNA2-WT and CTNNA2-MT LUAD patients in the LUAD cohort of TCGA (see Materials and Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the gene levels of a disintegrin and metalloprotease 23 (ADAM23) in central memory B cells, Fc fragment of IgA receptor (FCAR) and L1 cell adhesion molecule (L1CAM) in macrophages, adenylate cyclase activating polypeptide 1 (ADCYAP1) and sialic acid binding Ig-like lectin 6 (SIGLEC6) in mast cells, and GATA binding protein 3 (GATA3) in Th2 cells were found to increase ( Figure 2D ). Among them, ADAM23 is considered to be a possible tumor suppressor gene and is often downregulated in various malignant tumors ( Zmetakova et al, 2019 ). In addition, we used the cancer testis antigen (CTA) immune scoring system to score CTNNA2-WT and CTNNA2-MT LUAD patients in the LUAD cohort of TCGA (see Materials and Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Verbisck et al [ 29 ] demonstrated that cancer cells not expressing ADAM23 had higher migration capacities. Thus, the gene has been associated with multiple types of cancer, including breast cancers [ 30 , 31 ]. In addition, Elizondo et al [ 32 ] have demonstrated ADAM23 involvement in immune function has the expression of ADAM23 in dendritic cells governs T cell proliferation and cytokine production.…”
Section: Resultsmentioning
confidence: 99%
“…Verbisck et al [29] demonstrated that cancer cells not expressing ADAM23 had higher migration capacities. Thus, the gene has been associated with multiple types of cancer, including breast cancers [30,31]. In addition, Elizondo et al [32] have demonstrated https://doi.org/10.1371/journal.pone.0237818.g003…”
Section: Plos Onementioning
confidence: 99%
“…A disintegrin and metalloprotease 23 ( ADAM23 ), a member of the ADAM family, is considered a possible tumour suppressor gene, 36 and is frequently down‐regulated in various types of malignancies 37,38 . The silencing or decreased methylation of ADAM23 gene often associated with advanced disease and metastasis in different types of tumours, 39,40 including colorectal cancer 41 .…”
Section: Discussionmentioning
confidence: 99%